Effect of Bifidobacterium bifidum supernatant on the morphological and functional characteristics of human fibroblasts in real time during an in vitro experiment - A. A. Markov; E. G. Kostolomova; T. Kh. Timokhina; G. S. Solovyev; Ya. I. Paromova; E. D. Polyanskih; K. A. Voronin (Медицинская иммунология, 2023)
Currently, there is an active search for exogenous stimulators of repair and regeneration processes. In the recent decades, some data on the immunotropic activity of bifidobacteria have been accumulated. The key role in healing of wound defects belongs to fibroblasts due to the secretion of the extracellular matrix components, metabolites, signal factors for the surrounding cells, and tissue metabolism regulation. The paper presents the results of the study of the effect of Bifidobacterium bifidum supernatant (10 ml/mL) on the morphological and functional properties of human fibroblasts in real time during the in vitro experiment. In our work, we used the reference strain B. bifidum 791 (All-Russian Collection of Industrial Microorganisms of the State Research Institute for Genetics and Selection of Industrial Microorganisms “Genetika”, Deposit No. AS-1247) used in the production of the probiotic product “Bifidumbacterin” (ZAO “Ecopolis”, the city of Kovrov), and adult human fibroblasts (cell line LECH-4 (81)) (laboratory of cell cultures ENIIVI, the city of Yekaterinburg). Structural and functional studies were conducted on co-culture days 1, 3, 7, 14, 21, and 28. The products of B. bifidum secondary metabolism have a stressful effect on the morphological and functional state of fibroblasts on the first day. The processes of proliferation are stimulated in the culture in the experiment (2.67±0.24) compared with the control group (0.75±0.15) (p < 0.01) without blocking apoptosis in the cell. This leads to the increase in the production of extracellular matrix proteins, both collagen (pg/mL) (400±19 against 110±25 in the control group), and elastin (ng/mL) 395±30 and 125±29). Co-culture of fibroblasts within 24 hours in the experimental sample leads to a massive “release” of the CD44 receptor (p < 0.05), compared to the control group which is confirmed by phenotypic changes (r = 0.66). The decrease of CD105+, CD44+ receptors (p < 0.05), compared with the control group and the increase of CD29+ expression (p < 0.05) is observed on days 1 and 3. Activated fibroblasts have an altered secretory phenotype that produces cytokines of various types such as TGF-b (r = 0.78), IL-6 (r = 0.57), IL-1b (r = 0.75), IL-8 (r = 0.63). The maximum adaptation of cells in the experimental system is registered on the 7th day, which correlates with morphometric (r = 0.59) and cytometric (r = 0.71) studies. The received data contribute to understanding of the mechanisms of the immunoregulatory influence of normal biota (in the bifidobacteria model) on the repair and regeneration processes.